Pendidikan Multikultural Paradigma Moderasi Beragama Perspektif Imam Al-Ghazali - Irmawati, Irmawati; Mardiana, Dina (Hikmah, 2024)
This research aims to analyze Imam al-Ghazali's thoughts as the foundation of the paradigm of religious moderation in multicultural education. Imam al-Ghazali is a prominent scholar who advocates views that support religious moderation, tolerance, and interfaith harmony. This research uses the literature method to analyze and summarize Imam al-Ghazali's thoughts and understand how these views can be applied in the context of multicultural Islamic Religious Education. The research findings show that Imam al-Ghazali's thought reflects a strong paradigm of religious moderation. He emphasized the importance of a balanced understanding of religion, as well as values such as tolerance, compassion and peace in Islam. These concepts have significant relevance in the context of a multicultural society, where religious and cultural differences are an unavoidable reality. Islamic education based on Imam al-Ghazali's thought can play an important role in promoting better interfaith understanding, reducing conflict, and building harmonious relationships in multicultural societies. This research underscores the importance of revitalizing the paradigm of religious moderation in Islamic education and integrating it into the Islamic education curriculum. The implications of this research highlight the need for efforts in developing Islamic education that emphasizes the values of religious moderation as a path to a more inclusive, tolerant and peaceful society in the era of multiculturalism.